Optimization of the antireflecting effect of heat-reflecting coatings - Bainov D. D. Dashi Dambaevich (2004, 2004)
The method of optimization of the antireflection effect of heat-reflective coatings was described. The evolution method used in the calculations consists in choosing the thickness values of antireflecting layers of a multilayer coating to obtain the strongest antireflecting effect in the visible spectral region. It was shown that, to reach high values of the transmission factors, it was helpful to separate one silver layer into two with an interlayer of antireflecting oxide films between them. The calculation data on the transmission and reflection from the coatings were presented and their structures mentioning the layer thickness were given/